2016
DOI: 10.1186/s12887-016-0738-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early measles vaccination at 4.5 months of age on growth at 9 and 24 months of age in a randomized trial in Guinea-Bissau

Abstract: BackgroundProviding an early, additional measles vaccine (MV) at 4.5 months of age has been shown to reduce child mortality in low-income countries. We studied the effects on growth at 9 and 24 months of age.MethodsA randomized controlled trial was conducted in Guinea-Bissau from 2003–2007 including 6,648 children. Children were randomized 1:1:1 to receive Edmonston-Zagreb measles vaccine at 4.5 and 9 months of age (group A), no vaccine at 4.5 months and Edmonston-Zagreb measles vaccine at 9 months (group B), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Serologic and epidemiologic studies suggest that 1-dose measles vaccine efficacy is approximately 85%-90% when given at nine months of age and that 2-dose effectiveness is >99% when the second dose is given at ≥12 months of age. A two-dose measles vaccination schedule might reduce not only child mortality but also improve growth [10]. This may confirm the previous studies on vaccination coverage in other parts of the world which shown socioeconomic status, insecurity, cultural diversity, community attitude towards measles and religion plays an important reason for lack of vaccine covered [25,26].…”
Section: Sci Forschensupporting
confidence: 81%
See 1 more Smart Citation
“…Serologic and epidemiologic studies suggest that 1-dose measles vaccine efficacy is approximately 85%-90% when given at nine months of age and that 2-dose effectiveness is >99% when the second dose is given at ≥12 months of age. A two-dose measles vaccination schedule might reduce not only child mortality but also improve growth [10]. This may confirm the previous studies on vaccination coverage in other parts of the world which shown socioeconomic status, insecurity, cultural diversity, community attitude towards measles and religion plays an important reason for lack of vaccine covered [25,26].…”
Section: Sci Forschensupporting
confidence: 81%
“…A second dose of measles-containing vaccine given during supplemental immunization activities played a vital role in raising the population's immunity levels. However, routine vaccination coverage remains low, and health systems are still weak [9,10]. The previous study showed that 86.8% of children were positive for the anti-measles virus-specific IgM antibodies [11].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study investigating the effect of early MV on anthropometrics found that early MV was associated with larger MUAC at 24 months of age after both groups had (also) received the 9 months MV, especially for girls (13). The effect was not detectable at 9 months of age.…”
Section: Consistency and Contradictions With Other Studiesmentioning
confidence: 82%
“…However, humoral immunogenicity is reduced when measles vaccination is administered at 6 months, with an average seroconversion rate of 76% compared with 92% at 9 months [ 37 ]. As a result, vaccine effectiveness has been demonstrated to be lower in those under 9 months but whether or not administration would still be beneficial in terms of reducing disease severity and overall morbidity is an ongoing discussion [ 2 , 11 , 37 , 38 , 39 , 40 , 41 ]. Meta-analysis suggests that antibody levels are reduced in infants immunized before 9 months even after subsequent MCV1 and MCV2 vaccination, while differences in seropositivity, T cell responses, and vaccine effectiveness are not seen [ 42 ].…”
Section: Discussionmentioning
confidence: 99%